2010
DOI: 10.1299/jmmp.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Effect on Whisker Orientation Dependence of Composite Strength of Aluminum Cast Alloy Reinforced by Al2O3 Whiskers and SiC Particles

Abstract: The hybrid effect on the orientation dependence of the composite strength of an aluminum cast alloy reinforced by Al 2 O 3 whiskers and SiC particles is studied experimentally and numerically. Two types of specimens are prepared for monotonic bending tests. The longitudinal specimen orientation (maximum stress direction) is parallel to or normal to randomly oriented whiskers in plane. The monotonic strength is 18% higher when the hybrid metal matrix composite (MMC) is subjected to an external load parallel to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The chemical composition of AC4CH alloy is listed in Table 1. As described in the previous report [18], due to the formation process of the preform the whiskers in the both MMCs are randomly oriented in a plane. 'Longitudinal cross section' is defined as the plane and 'lateral cross section' is defined as the one perpendicular to the plane in this article.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 66%
See 1 more Smart Citation
“…The chemical composition of AC4CH alloy is listed in Table 1. As described in the previous report [18], due to the formation process of the preform the whiskers in the both MMCs are randomly oriented in a plane. 'Longitudinal cross section' is defined as the plane and 'lateral cross section' is defined as the one perpendicular to the plane in this article.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 66%
“…It may also merely be the result of the load sharing between the high-modulus reinforcement and the low modulus matrix [16]. The fracture mechanism of cast hybrid MMCs under monotonic and cyclic loads was investigated by Rafiquzzaman et al [17,18], who observed fracture surfaces and concluded that the fracture under cyclic load was dominated by interfacial debonding at particle/matrix and whisker/ matrix interfaces. This interfacial debonding occurred due to the cyclic hardening caused by the accumulation of plastic strain at the interface between matrix and reinforcement.…”
Section: Introductionmentioning
confidence: 99%